STRATEGI INOVASI DAN KEBERLANJUTAN BISNIS URUSAN COFFEE: MENEMBUS PASAR KOPI INDONESIA - Pamungkas, Giantoro; Nurlelah, Nurlelah (Yayasan Education and Social Center, 2025)
The coffee industry in Indonesia continues to experience significant growth, driven by high domestic consumption and the trend of coffee globalization. In this case, Urusan Kopi comes as a business that focuses on coffee-based product innovation. Urusan Kopi is a coffee-based business that aims to introduce local coffee products with unique innovations and differentiation, such as blending coffee with natural ingredients and local spices. This research explores business strategy, product innovation, and sustainability in the coffee industry in Indonesia. With a SWOT approach and competitor analysis, Urusan Kopi targets a niche market that cares about local and environmentally friendly products. The methods used were customer satisfaction survey, business performance analysis, and digital marketing strategy evaluation. The results show great potential to compete with big brands through product differentiation, digital marketing, and strategic distribution. The findings are relevant to the development of small and medium-sized enterprises in the coffee industry.